The new colombian symphonic and choral music (2013)
The academic development that, in the area of ​​music, has taken place in the symphonic musical composition in the country, has made a significant number of composers flourish that account for a large volume of works of different formats. These works deserve to be studied, analyzed, played in public, recorded and disseminated, both nationally and internationally. Our project that still continues, has consisted of a methodology to collect, analyze, study, rehearse and record Colombian works that, through the same investigative process, can be described as a level of international competence, in order to make known its artistic and aesthetic value. Indeed, we want to leave posterity the sound testimony of works that, having been executed a greater number of times and having escalated to a certain notoriety, some of them; some others that have achieved a decent premiere in the country or others that have been able to reach a first audition but without sufficient public or specialized criticism and, like the previous ones, do not yet have sound records.